The role of mineralocorticoid receptor antagonists in the prevention and treatment of chronic heart failure after acute myocardial infarction (Texas Journal of Medical Science, 2023)
This review article examines the role of mineralocorticoid receptor antagonists (AMP) in the treatment of heart failure (CH) in patients who have suffered acute myocardial infarction (AMI). The pathogenetic basis of the effect of AMPs on myocardial remodeling after AMI is considered. The pharmacological characteristics of drugs of this class are described: spironolactone and eplerenone. The results of the main studies proving the protective role of eplerenone in patients who have suffered AMI with HF of varying severity (EPHESUS, EMPHASIS-HF, ALBATROSS, REMINDER) are covered. The effectiveness of eplerenone was analyzed depending on the timing of its administration. The safety of the drug in comparison with spironolactone was considered. In conclusion, it was concluded that it is advisable to use these drugs in routine therapy in acute, subacute and long-term periods of ST-segment elevation AMI and with a left ventricular ejection fraction ≤40%, heart failure or diabetes mellitus, when patients already receive angiotensin-converting enzyme inhibitors and beta blockers and in the absence of renal failure or hyperkalemia. In this case, preference should be given to eplerenone as a drug having the most convincing evidence base and having a favorable tolerance profile. The introduction into medical practice of effective, accessible generics of eplerenone allows expanding its use in real clinical practice